Outcome of Cesarean Myomectomy: Is it a Safe Procedure? - Senturk, Mehmet Baki; Polat, Mesut; Doğan, Ozan; Pulatoğlu, Çiğdem; Yardımcı, Oğuz Devrim; Karakuş, Resul; Tayyar, Ahter Tanay (Geburtshilfe und Frauenheilkunde, 2017)
Objective Myomectomy performed during cesarean section is still controversial because of the potential for associated complications, especially with large myomas. Many obstetricians avoid performing cesarean myomectomy procedures because of the risk of uncontrollable hemorrhage. However, the prevalence of pregnant women with myomas is increasing, leading to an increase in the likelihood that physicians will encounter this issue. The aim of this study was to compare outcomes and complications of patients who either had or did not have cesarean myomectomy.Method A total of 361 patients were evaluated in this retrospective study. Patients who had cesarean section with myomectomy and patients had cesarean section without myomectomy were compared with regard to demographics, drop in hemoglobin levels, complications, blood transfusion rates and duration of operation. These parameters were also compared when the diameter of the myoma was larger than 5 cm. Values of p < 0.01 and p < 0.05 were considered statistically significant.Results While maternal age and gravidity were similar in both groups (p > 0.05), the mean myoma diameter was smaller and the duration of operation was longer in the group who underwent cesarean myomectomy (p < 0.05). The reduction in hemoglobin level, rate of complications, and number of transfusions were similar in both groups (p > 0.05).Conclusion This study shows that myomectomy during cesarean section does not increase complications or transfusion rates and appears to be a safe procedure.
Keywords: cesarean section; cesarean myomectomy; complications; myoma